Design and Development of a Door Access Prototype Using a Voice Recognition and Password Module Based on the NodeMCU ESP32 - Putri Nur Azmina; Nini Firmawati (Talenta Publisher, 2026)
Door access security is an important aspect of room protection systems, yet conventional locking methods still have limitations in preventing unauthorized access. This study designed and implemented a NodeMCU ESP32-based smart door prototype integrating voice recognition and password authentication to provide a dual-layer authentication mechanism for smart door access. The system consists of a NodeMCU ESP32 as the main controller, a voice recognition module for voice input, a keypad for password entry, a relay as an actuator, a solenoid door lock as the locking mechanism, and an LCD to display system status. The voice recognition module detects previously trained and stored voice commands to grant access, while unregistered voices are rejected automatically. The keypad password serves as a secondary layer of security. The system was evaluated based on voice recognition performance at different distances and environmental conditions, including quiet, normal, and rainy conditions. Experimental results show that the voice recognition module can detect voices effectively at distances up to 1,250 cm in quiet conditions, 400 cm in normal environments, and 100 cm in noisy or rainy conditions. Overall, the prototype successfully implemented a dual-security access mechanism combining voice recognition and password authentication, while providing additional real-time security monitoring through the integrated system.